NATIONAL VALUES - THE IDEOLOGICAL BASIS OF SPIRITUAL EDUCATION (Scientific journal of the Fergana State University, 2023)
In this article, the ideas of educating the young generation, who are our future, as perfect human beings based on national and spiritual values, are scientifically analyzed. Today, in the turbulent times, only a truly spiritual and enlightened person can know the value of a person, realize his national values, national identity, live in a free society, and selflessly fight for our independent country to take its rightful place in the world community.Therefore, parents, teachers-coaches, it is necessary not to lose responsibility for education of young people and not to be negligent.It should not be forgotten that the great future of the state is directly related to educating young people with deep knowledge and pure morals. In general, it is impossible to imagine the development of science and culture, which is directly related to the improvement and development of people's life, without education. This is a scientific-theoretical, philosophical-educational truth proved by our ancestors.